An Explanatory Factor Analysis on Islamic High School Students’ Level of Digital Literacy in Islamic Boarding School Environment - Ridhoi, Moh. (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to measure and analyze the explanatory factors that influence the level of digital literacy among Madrasah Aliyah students (santri) within Islamic boarding schools (pondok pesantren) in Gresik Regency. Digital literacy among santri has become an important issue in modern Islamic education, as it relates to their ability to access, understand, and utilize technology ethically and productively. This research employs a quantitative approach using a survey method, and data analysis was conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) model involving 134 respondents from four Islamic boarding schools in Gresik Regency. The results of the analysis show that the five main constructs—digital skill, digital information processing, digital safety & ethics, digital communication & collaboration, and digital religious engagement—significantly influence the level of santri digital literacy with p < 0.05. The dimension of digital safety & ethics has the highest influence (O = 0.250; T = 9.298), followed by digital religious engagement (O = 0.275; T = 11.763), digital skill (O = 0.225; T = 15.718), digital communication & collaboration (O = 0.268; T = 12.606), and digital information processing (O = 0.192; T = 8.978). The overall mean score of santri digital literacy is 4.14, indicating a high category. These findings confirm that santri possess good digital literacy skills; however, they still require continuous guidance particularly in the aspects of digital ethics and the utilization of technology to strengthen Islamic values in the digital era.